في الوحدات الحكومية COBIT تقويم إجراءات الرقابة الداخلية وفق إطار: دراسة تحليلية - كبرى محمد طاهر; عبدالصمد جاسم محمد (PROSPECTIVE RESEARCHES, 2023)
The world witnessed great developments in the field of information and communication technology, and that technology was used in many business and service sectors, and the government sector had a prominent share of this development. Paying attention to the internal control system in order to ensure the performance of the institution. Therefore, the institutions are keen on the importance of keeping pace with the internal control system of the requirements of information technology and the continuous developments of these systems. The need for evaluating internal control procedures to keep pace with the developments and changes that occur upon the application of information technology, and procedures have emerged. The internal control is compatible with the developments of information technology and is in accordance with international standards and the use of modern internal control frameworks, the most prominent of which is the (COBIT framework). The study concluded that the COBIT framework is suitable for evaluating internal control procedures in government units.